Experimental results on the high-pressure phase diagram of boron nitride. (1st December 2022) - Fukunaga, Osamu; Nakano, Satoshi; Taniguchi, Takashi
Abstract: We present the boron nitride (BN) phase diagram at 3–6 GPa and 1100 °C–2200 °C using a modified belt-type high-pressure apparatus. The cubic BN (cBN)–hexagonal BN (hBN) phase boundary was determined using the hBN–Mg3 BN3 catalyst system as a starting material at 4–5.5 GPa. Additional experiments were conducted at 3–4 and 4–6 GPa using cBN powder or hBN–Ca3 B2 N4 catalyst as a starting material. In the hBN–catalyst system, the rate of cBN nucleation was reduced by the growth of metastable hBN crystals under the cBN-stable pressure–temperature conditions. The stable BN phases were identified from the samples reacted with a longer run duration. The phase boundary line between hBN and cBN was determined as the equation P (GPa) =  T (°C)/400 + 0.3, which agreed with the boundary lines calculated by Gruber and Grüneis and by Nikaido et al.